ORGANIZING THE EFFECTIVE USE OF AGRICULTURAL LAND IN THE CONDITIONS OF WATER SHORTAGE (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
The article analyzes the issues of organizing the effective use of agricultural land in conditions of water scarcity. Modern mechanisms for managing land and water resources in the context of climate change, limited water resources, and degradation of irrigated lands are highlighted. The effectiveness of water-saving technologies, optimization of crop composition, digital monitoring, and agrotechnical measures is scientifically substantiated. The results of the study will serve to increase the efficiency of agricultural land use and sustainable management of water resources